Humanitarian Architecture: Examining the Perspective of Architecture Faculties and Students - Yenny Rahmayati; Haya Alshammari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The frequency of natural disasters keeps increasing from time to time. The catastrophes from the events affect millions of people around the world. It demands the involvement of architects in the design and planning difficulties associated with rebuilding post-disaster areas and cities. However, there is a continuing lack of architects who are capable of handling the damage left behind by devastating natural disasters like floods, fires, earthquakes, typhoons, and tsunamis. In addition, there is a shortage of architectural students who are interested in this crucial matter. Targeting architecture faculties and students, this study discusses the architects’ role in the humanitarian subject. The objective is to figure out the level of awareness and exposure to this topic at the higher education level. It was done by examining the involvement of architecture faculties and students in humanitarian architecture through mixed qualitative and quantitative methods. This study proposes a way to shed light on humanitarian architecture to alert architecture faculties and students to the growing need for help and support in reconstructing communities damaged by catastrophes. It also provides an understanding of how to offer assistance while respecting the culture, identity, and needs of the affected people.